G600(P) Child health promise: good ideas brought together – childhealthpromise.org. (May 2019) - Race, H; Collier, L; Singh, G; Sen, C
Abstract : Aim: Child Health Promise (CHP) is a website set up in collaboration with the Royal Society of Medicine (RSM) to share paediatric quality improvement projects. Background: As a paediatric trainee, moving around different hospitals and community settings can be frustrating as lots of quality improvement work is repeated, cut short and not shared. The CHP website enables you to quickly create your own project page without having to set up your own website. The projects are all displayed on the CHP website enabling you to disseminate your work. The aim is to inspire, invite others to join and point out both the positives and pitfalls of your project so everyone can learn. Methods: We wrote the material for the website to include separate sections explaining the concept for health care professionals, young people and parents. Currently, you can only register to upload a project with an nhs.net email address to avoid safeguarding issues. You then fill in a short form based on SMART objectives about your project, upload photographs and resources. Your project is then displayed on the project page. This is open to the public and other health care professionals to view. The website is funded by the RSM. Results: Healthcare professionals from across the UK have uploaded a total of 25 projects in the last 6 months ranging from ' Restart a heart – community resuscitation training for children' to ' Asthmanauts are go' – a comic for children explaining asthma. Three projects were presented at the Child Health Festival, a joint conference with RCPCH, British Association for Child and Adolescent Public Health and the RSM about advocating for child health. Discussion: By collaborating with healthcare professionals, young people have been involved in developing and running their own community based projects. We would like CHP to support co-production of sustainable quality improvement projects. Conclusion: We hope that CHP changes the culture of quality improvement promoting collaboration between healthcare professionals and the public and across traditional boundaries. Ultimately, this should allow great ideas to be shared and developed together.